APLIKASI PENGENALAN BENDA SEKITAR UNTUK ANAK AUTIS BERBASIS ANDROID - Tomi Wingga Pratama; Indah Puji Astuti; Ghulam Asrofi Buntoro (Universitas Muhammadiyah Ponorogo, 2019)
Ceria Centre is one of the institutions engaged in the consultant psychologist and there are some participants who are experiencing autism. When observing the information, the autistic child requires media for the identification of the surrounding objects that are visual and audio. In this institution in the presentation of the introduction of objects for autistic children still use traditional tools, namely the form of beams. This way is considered less efficient because it often breaks or loss of the introduction beam and does not cover the possibility of human error as well. The author devised an interactive Android-based recognition application as a media helper of the introduction of objects around by loading the needs required by the autistic child, by giving a simple look that contains the introduction of alphabets, numbers, Limbs, animals, fruit and spelling of words and accompanied by audio. This application is designed using construct 2 using the waterfall development method. This research generates an Android-based object recognition application designed according to what the autistic child needs. In general this application can make it easier for children to increase their knowledge with a percentage of 70%.